Performance of pine cone seedlings in different doses of phosphate fertilizing - Carvalho, Jullyanna Nair de; Silva Carvalho, Júnia Naara da; Carvalho, Pollyanna Aparecida de; Basílio, Letícia Silva Pereira; Lima, Augusto Miguel Nascimento; Pio, Rafael (Comunicata Scientiae, 2022)
Adding phosphorus in the composition of the substrate for the seedlings production contributes to a faster growth of seedlings, increases the resistance to biotic and abiotic stresses, also improves the efficiency in the use of nutrients and water in many vegetal species. The objective of this research was to evaluate the vegetative growth and quality of Annona squamosa L. seedlings, propagated by seeds, regarding the application of single superphosphate in enriched sugarcane bagasse substrate. The completely randomized design consisted of six treatments arranged according to the following application doses (0; 0.75; 1.5; 2.25; 3.0 and 3.75 kg), using the single superphosphate in substrate, with four replicates per treatment. At 120 days after sowing, number of leaves, leaf area, shoot height, stem diameter, shoot dry mass, root dry mass, total dry mass, ratio between shoot dry mass and root dry mass, chlorophyll a, chlorophyll b, total chlorophyll, and Dickson’s Quality Index were evaluated. The maximum growth of the pine cone plants were noted when added single superphosphate to the substrate in doses ranging from 0.6 to 1.2 kg.m-3. The phosphate fertilizer favored the growth especially of the roots and leaf area and improved the quality of pine cone seedlings.